Detestable and wicked arts: New England and witchcraft in the early modern Atlantic world - Moyer, Paul Benjamin (Cornell University Press, 2020)
Introduction : The Devil in New England -- "Hanged for a Witch" : Witch-hunting in New England before 1670 -- "Being instigated by the Devil" : The Crime of Witchcraft -- "A forward, discontented frame of spirit" : The New England Witch -- "The more women, the more witches" : Gender and Witchcraft -- "There was some mischief in it" : The Social Context of Witchcraft -- "Very awful and amazing" : Witch Panics and the Bewitched -- "According to God's Law" : Witch-hunting as a Judicial Process -- Conclusion : The Case of Ann Burt and Witch-hunting in the English Atlantic.